Farnesylthiosalicylic acid-derivatized PEI-based nanocomplex for improved tumor vaccination - Yuang Chen; Yixian Huang; Haozhe Huang; Zhangyi Luo; Ziqian Zhang; Runzi Sun; Zhuoya Wan; Jingjing Sun; Binfeng Lu; Song Li (Elsevier, 2021)
Cancer vaccines that make use of tumor antigens represent a promising therapeutic strategy by stimulating immune responses against tumors to generate long-term anti-tumor immunity. However, vaccines have shown limited clinical efficacy due to inefficient delivery. In this study, we focus on vaccine delivery assisted by nanocomplexes for cancer immunotherapy. Nanocomplex-mediated vaccination can efficiently deliver nucleic acids encoding neoantigens to lymphoid tissues and antigen-presenting cells. Polyethylenimine (PEI) was conjugated with farnesylthiosalicylic acid (FTS) to form micelles. Subsequent interaction with nucleic acids led to formation of polymer/nucleic acid nanocomplexes of well-controlled structure. Tumor transfection via FTS-PEI was much more effective than that by PEI, other PEI derivatives, or naked DNA. Significant numbers of transfected cells were also observed in draining lymph nodes (LNs). In vivo delivery of ovalbumin (OVA; a model antigen) expression plasmid (pOVA) by FTS-PEI led to a significant growth inhibition of the OVA-expressing B16 tumor through presentation of OVA epitopes as well as other epitopes via epitope spreading. Moreover, in vivo delivery of an endogenous melanoma neoantigen tyrosinase-related protein 2 (Trp2) also led to substantial tumor growth inhibition. FTS-PEI represents a promising transfection agent for effective gene delivery to tumors and LNs to mediate effective neoantigen vaccination.